2019
DOI: 10.1039/c8nr08442d
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing tumor chemotherapy and overcoming drug resistance through autophagy-mediated intracellular dissolution of zinc oxide nanoparticles

Abstract: Enhancing tumor chemotherapy and overcoming drug resistance through autophagy-mediated intracellular dissolution of zinc oxide nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 67 publications
1
38
0
Order By: Relevance
“…The induction of autophagy has also been observed following treatment with different types of nanoparticles, such as silica nanoparticles, silver nanoparticles, and others [50,53]. Autophagy is activated in human cancer cells by zinc oxide nanoparticles, which are currently under development for use in enhancing tumor chemotherapy and overcoming drug resistance [54]. Quantum dots are also currently under development for use in a broad range of biomedical imaging applications and have been shown to induce lysosome-dependent autophagy activation, ROS production, and toxicity in human hepatocytes [55].…”
Section: Autophagy Dysfunction Induced By Nanomaterialsmentioning
confidence: 99%
“…The induction of autophagy has also been observed following treatment with different types of nanoparticles, such as silica nanoparticles, silver nanoparticles, and others [50,53]. Autophagy is activated in human cancer cells by zinc oxide nanoparticles, which are currently under development for use in enhancing tumor chemotherapy and overcoming drug resistance [54]. Quantum dots are also currently under development for use in a broad range of biomedical imaging applications and have been shown to induce lysosome-dependent autophagy activation, ROS production, and toxicity in human hepatocytes [55].…”
Section: Autophagy Dysfunction Induced By Nanomaterialsmentioning
confidence: 99%
“…The final version may differ from this version. indicating that these NMs triggered pro-death autophagy (Hu et al 2019). This was suggested to be a positive effect of NMs in cancer therapy through the regulation of oxidative stress and autophagy, which led to cell death.…”
Section: Positive Turn-on Effects: Pro-death Nature Of Autophagymentioning
confidence: 88%
“…The nanocarrier including ZnO enhanced the infiltration of T cells into the tumor tissue compared to mice immunized with PLLA fibers directly conjugated with tumor antigen. Recently, Hu et al [112] showed an enhanced antitumor therapeutic effect in in vivo animal models injected with 4T1 tumor cells, especially in a combinatorial administration with ZnO NPs and doxorubicin (DOX). It was demonstrated that ZnO NPs promoted Atg5-regulated autophagy flux suggesting that autophagy induction by ZnO reinforces cancer cell death by increased Zn ion release and ROS generation when combined with DOX.…”
Section: Zinc Oxide Nanoparticlesmentioning
confidence: 99%